Non-Penal Efforts to Overcome Crimes by Verbal Da'wah - Randi Eka Putra; Bisma Putra Pratama (Ekasakti Journal of Law and Justice, 2024)
This research is a legal research with specifications that are descriptive analytical. The implementation of verbal da'wah as a form of non-penal crime reduction in the jurisdiction of the South Coast Resort Police is to convey religious messages or moral values to others through words and oral communication. Conducted with I'tikaf, Da'wah, Weekly Recitation and Spiritual Flush activities. A persuasive approach by law enforcement officials to the community through activities carried out on community groups. Verbal da'wah is used to promote good deeds and positive activities in society, such as contributing to the general well-being, helping and avoiding harmful behavior. At events such as citizen gatherings, police can convey moral and ethical messages to participants. Giving Advice: Police officers may provide verbal advice to individuals involved in crimes or risky behavior. The impact of the implementation of verbal proselytizing as a form of non-penal crime reduction on the level of crime that occurs in the South Coast Resort Police Jurisdiction varies depending on the context, the message conveyed, and the recipient of the message. This da'wah approach looks quite effective characterized by Increasing Religious Awareness, Verbal da'wah can help individuals understand religious teachings better and increase their awareness of moral and ethical values. Positive Behavior Change, Da'wah can affect behavior change, such as reducing risky behavior, stopping criminal acts, or promoting social kindness and solidarity. The implementation of da'wah can benefit an individual's spiritual growth, help them search for meaning in life, and strengthen their relationship with their religion or belief.